1361. Lyme Borreliosis (LB) is a Significant Disease Burden in Germany: Estimated LB Incidence after Adjusting for Under-ascertainment by Public Health Surveillance, 2021. (15th December 2022) - Olsen, Julia; Brestrich, Gordon; Pilz, Andreas; Halsby, Kate; Kelly, Patrick; Malerczyk, Claudius; Angulo, Frederick; Stark, James H
Abstract: Background: Lyme borreliosis (LB), the most common tickborne disease in Europe, is endemic in Germany. Nine German states (with 42% of the German population) conduct LB surveillance with mandatory notification by clinicians and laboratories but an analysis of outpatient claims estimated that only one of every six LB cases in these states were reported. We estimated the LB incidence after adjusting for under-ascertainment of public health surveillance. Methods: Nationally representative studies estimated the prevalence of antibodies against Borrelia burgdorferi sensu lato in adults and children in Germany. Published estimates of the asymptomatic proportion and the duration of antibody detection were used to estimate the number of LB cases from seroprevalence data in states that conduct LB surveillance. The number of estimated LB cases were compared to the number of surveillance-reported cases to derive under-ascertainment multipliers for adults and children. The derived multipliers were applied to the number of reported cases in 2021 to estimate the number and incidence of LB cases in the states that conducted surveillance in 2021. A sensitivity analysis evaluated the impact of different antibody durations. Results: Using a 50% asymptomatic proportion and 10-year antibody duration, the estimated number (population-based incidence) of LB cases in states that conducted surveillance was 128, 870 (408/100, 000) in 2021. Since there were 11, 051 reported cases in these states, these data indicate there were 12 LB cases in 2021 for every reported case in these states. Using 20-year or 5-year antibody duration, the estimated number (incidence) of LB cases in the states that conducted surveillance was 64, 935 – 259, 740 (204 - 816/100, 000) in 2021, respectively. Conclusion: Incidence of LB in states that conduct surveillance in Germany is higher than reported. Under-ascertainment of LB cases in states that conduct surveillance is even greater than that estimated in a claims data analysis of medically-attended LB cases. Enhancements of LB surveillance, including expanding nationwide, would facilitate further elucidation of the true LB disease burden in Germany. Disease prevention efforts, including availability of an efficacious vaccine, are needed to address this important public health problem. Disclosures: Julia Olsen, BS, Pfizer: Employee Gordon Brestrich, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Andreas Pilz, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds|Pfizer: Stocks/Bonds Kate Halsby, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Patrick Kelly, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Claudius Malerczyk, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds Frederick Angulo, DVM PhD, Pfizer: Employee|Pfizer: Stocks/Bonds James H. Stark, PhD, Pfizer: Employee|Pfizer: Stocks/Bonds.